Nexus Between Carbon Emissions, Energy Consumption, Urbanization and Economic Growth in Asia: Evidence From Common Correlated Effects Mean Group Estimator (CCEMG) - Adeneye, Yusuf Babatunde; Jaaffar, Amar Hisham; Ooi, Chai Aun; Ooi, Say Keat (Frontiers in Energy Research, 2021)
This study investigates the dynamic relationships between carbon emission, urbanization, energy consumption, and economic growth in a panel of 42 Asian countries for the period 2000-2014 using dynamic common correlated effects panel data modeling. This study employs second generation cross-sectional Pesaran (2007) panel unit root, Westerlund panel cointegration tests (2007), and Pesaran’s (2006) common correlated effects mean group estimation technique. These approaches allow for cross-sectional dependence, and are robust to the presence of common factors, serial correlation, and slope heterogeneity. The CCEMG test reveals that the high average coefficient of 0.602 between carbon emission and energy consumption while low coefficients of 0.114 and 0.184 for the pairs of carbon emission-urbanization and carbon emission-GDP, respectively for the panel as a whole, suggesting a cointegration between carbon emission, urbanization, energy consumption, and economic growth. The results indicate that there is relatively high carbon emission especially for highly populated and geopolitical risk Asian countries in the short run, while long run relationship is maintained, which is due to the on-going carbon taxation and energy prices. Our results are robust to PMG-ARDL estimator. Overall, these findings cast important implications on renewable energy policy and urban planning insights for the policymakers.